Identification of peneplains by multi‐parameter assessment of digital elevation models. Issue 11 (6th April 2015) - Haider, Vicky L.; Kropáček, Jan; Dunkl, István; Wagner, Bianca; von Eynatten, Hilmar
ABSTRACT The concept of peneplains has existed since the end of the nineteenth century. Typical peneplains are elevated geomorphological features with a low relief surface on top. They may be tilted due to tectonic activity or intersected by evolving erosion. Until now neither a standardized definition for peneplains, nor an established procedure to identify and quantify well preserved peneplains as prominent landforms existed. At present the global availability of homogeneous digital elevation models (DEMs) provides an accurate characterization of the morphology of the Earth surface. In this study a new, numerical, DEM‐based fuzzy‐logic approach is presented for the delineation of peneplains solely from a morphological perspective. The approach is based on a morphometric analysis of the 90‐arcsec Shuttle Radar Topography Mission (SRTM) DEM. Four critical parameters are employed which are implemented within a geographic information system (GIS). The parameters for the correct and unambiguous description of a 'flat top mountain' are: (i) slope, (ii) curvature, (iii) terrain ruggedness index, and (iv) relative height. The approach was developed using a test area in the central Tibetan Plateau, which is characterized by representative and well preserved peneplains and for which additional field data were collected. In order to verify the method, peneplains were delineated in different regions with various geological settings for which potential peneplains were already described in the literature. The results from the Appalachian Mountains, Andes, Massif Central, and New Zealand confirm the robustness of the proposed approach. Copyright © 2015 John Wiley & Sons, Ltd.